O37 Carotid surgery during the COVID-19 pandemic. (30th July 2021) - Busuttil, A; Jacob, L; Elanwar, S; Lim, C. S; Baker, D. M
Abstract: Introduction: The aim of this prospective study was to evaluate the efficacy and safety of carotid endarterectomy for symptomatic carotid stenosis during the COVID-19 pandemic. Method: Re-organisation of stroke services due to the COVID-19 pandemic resulted in carotid endarterectomy for symptomatic disease being performed in two hospitals; Covid-19 free and non-free sites. Patients were referred from multiple online regional neurovascular multi-disciplinary team meetings, and managed according to the pre-Covid-19 guidance. All patients referred for carotid endarterectomy between 23 March 2020 and 31 July 2020 were included. Demographic, medical history, imaging, peri-operative, complication and follow-up data were collected and analysed prospectively. Result: 28 patients were referred for carotid endarterectomy, of whom 21 patients underwent surgery. The mean time to surgery was 11 days (3–35). The technical success rate was 100%. Peri-operatively and within 30-days post-operatively, no patient suffered death or stroke. There were 2 minor complications; one non-ST elevation myocardial infarction, and another wound haematoma and infection requiring readmission for antibiotics. No patient developed new COVID-19 infection post-operatively. Of the 7 patients not operated on; 2 were medically unfit for surgery, three declined surgery, and two had free floating thrombus that was managed successfully with anti-coagulation. Conclusion: During the pandemic, the provision of carotid endarterectomy for symptomatic carotid diseases was carried out safely and within the current recommendations, with several pre-cautionary measures being undertaken. Therefore, symptomatic carotid intervention should still be considered to reduce the risk of stroke provided similar pre-cautionary measures are undertaken. Take-home Message: Carotid surgery should continue during successive waves of the COVID-19 pandemic